2003
DOI: 10.1029/2001jd001210
|View full text |Cite
|
Sign up to set email alerts
|

Discrete measurements of reactive gases and fine particle mass and composition during the 1999 Atlanta Supersite Experiment

Abstract: [1] During the Atlanta Supersite Experiment (ASSE) in August 1999, a three-channel particle composition monitor (PCM) was used to measure PM 2.5 mass and composition as well as gas-phase NH 3 , HCl, HNO 3 , HONO, SO 2 , and acetic, formic, and oxalic acids over integrating periods of 10-24 hours. The period was characterized by stagnant periods associated with high temperatures, relative humidities, and UV radiation, underlying parameters causing photochemical activity with intense ozone, and PM 2.5 formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
(87 reference statements)
3
46
0
Order By: Relevance
“…This positive artifact is due to the adsorption of semi-volatile OC compounds onto the high surface area of the quartz fiber substrate of the OC filters (Mader and Pankow 2001). Previous studies have found the positive OC artifact to be 10-60% of the OC concentration (Turpin et al 2000;Subramanian et al 2004), and to be higher when sampling fresh, less photo-chemically oxidized emissions (Baumann et al 2003) or when sampling for short durations with little time for the filter to reach gas-particle phase equilibrium (Turpin et al 2000). Both of these conditions were present during the ACE-1 sampling sessions and likely contribute to the elevated OC artifacts observed.…”
Section: Ec-oc Analysismentioning
confidence: 99%
“…This positive artifact is due to the adsorption of semi-volatile OC compounds onto the high surface area of the quartz fiber substrate of the OC filters (Mader and Pankow 2001). Previous studies have found the positive OC artifact to be 10-60% of the OC concentration (Turpin et al 2000;Subramanian et al 2004), and to be higher when sampling fresh, less photo-chemically oxidized emissions (Baumann et al 2003) or when sampling for short durations with little time for the filter to reach gas-particle phase equilibrium (Turpin et al 2000). Both of these conditions were present during the ACE-1 sampling sessions and likely contribute to the elevated OC artifacts observed.…”
Section: Ec-oc Analysismentioning
confidence: 99%
“…Coincidentally, the factor 1.4 has been widely used in the past, originating from very limited theoretical and laboratory studies from more than 20 yr ago that suggested this value to be the lowest reasonable estimate for urban aerosols. 48 -50 More recent investigations, 51,52 however, suggest a factor of 1.6 Ϯ 0.2 and 2.1 Ϯ 0.2 to be more accurate in urban and nonurban environments during the summer, respectively. Our summer value is slightly lower and possibly indicative of this particular site being more heavily influenced by primary emissions from nearby industrial sources, making the influence from secondary atmospheric sources less important.…”
Section: Data Uncertaintiesmentioning
confidence: 99%
“…WSOC is extracted with 125 ml of pure water from the filter by sonication in a heated water bath (∼60 • C) (Baumann et al, 2003;Sullivan and Weber, 2006b) for 1.25 h. A portion of this sample (BB) was then fractionated into hydrophilic (HPHIL) and hydrophobic (HPHOB) components using a macro-porous nonionic resin (XAD-8) Solid Phase Extraction (SPE) column (Duarte and Duarte, 2005;Sullivan and Weber, 2006a). With the WSOC solution adjusted to pH=2 using HCl, the resin does not retain hydrophilic compounds.…”
Section: Extraction and Fractionation Of Biomass Burning Samplementioning
confidence: 99%